A comparison of DSM‐5 and ICD‐11 PTSD prevalence, comorbidity and disability: an analysis of the Ukrainian Internally Displaced Person's Mental Health Survey. (5th December 2017) - Shevlin, M.; Hyland, P.; Vallières, F.; Bisson, J.; Makhashvili, N.; Javakhishvili, J.; Shpiker, M.; Roberts, B.
Abstract : Objective: Recently, the American Psychiatric Association (DSM‐5) and the World Health Organization (ICD‐11) have both revised their formulation of post‐traumatic stress disorder (PTSD). The primary aim of this study was to compare DSM‐5 and ICD‐11 PTSD prevalence and comorbidity rates, as well as the level of disability associated with each diagnosis. Method: This study was based on a representative sample of adult Ukrainian internally displaced persons (IDPs: N = 2203). Post‐traumatic stress disorder prevalence was assessed using the PTSD Checklist for DSM‐5 and the International Trauma Questionnaire (ICD‐11). Anxiety and depression were measured using the Generalized Anxiety Disorder Scale and the Patient Health Questionnaire‐Depression. Disability was measured using the WHO Disability Assessment Schedule 2.0. Results: The prevalence of DSM‐5 PTSD (27.4%) was significantly higher than ICD‐11 PTSD (21.0%), and PTSD rates for females were significantly higher using both criteria. ICD‐11 PTSD was associated with significantly higher levels of disability and comorbidity. Conclusion: The ICD‐11 diagnosis of PTSD appears to be particularly well suited to identifying those with clinically relevant levels of disability.